THAIPUSAM RITUALS IN BANDA ACEH AS TAMIL HINDU ETHNIC IDENTITY - Cut Sofy Iramarisa; Aslam Nur; Ikhwan (The Department of Islamic History and Culture in cooperation with the Center for Islamic History and Culture in Aceh and Malay World Studies (PUSAKA), Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia, 2022)
The purpose of this study is to learn more about how the Thaipusam Tamil Hindu festival is celebrated in Banda Aceh, as well as how the people of Banda Aceh feel about it. The Thaipussam ritual is a Hindu religious ceremony that the Tamil ethnic minority follows. This ceremony is performed as a thank you to Lord Murugan or Lord Subramanyam, who gives life with safety, tranquility, and prosperity. This rite is also performed as a penance and on the day when vows are paid. This study employed a qualitative approach, including observation, interviews, and documentation as tools. The acquired data was analyzed using techniques such as data reduction, data presentation, conclusion drawing, and verification. The findings of this study show that the Thaipusam ritual is not just a religious activity for the Tamil people of Banda Aceh, but also an ethnic identity. Despite being a minority, this tradition makes the Tamil ethnic group's existence in Banda Aceh known, ensuring that ordinary people are not disturbed by the celebration. The contact between Tamil Hindus and other religious communities has never been tense or contentious. They all live in peace and love, never interfering with or mocking one another's religious beliefs.